Tolerance Amidst Multiculturalism in Society in the View of Hadith: A Study of Takhrij and Syarah Hadith - Tawil, Fatur Rahmat Saifullah; Sholeh, Ibnu (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the hadith about tolerance in a multicultural society. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the tolerance of Ahmad's history No. 2003. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi meets the qualifications of maqbul ma'mul bih for Islamic practice. This study concludes that the hadith narrated by Ahmad No. 2003 is relevant to use as an order to tolerate religion amid multiculturalism in society.